Coastal aquaculture development study, 1996 shirmp farm survey - Pham, Thuoc (SCP Fisheries Consultants Australia, 1996)
This report gives the results of the survey, including technical, social, environmental and economic aspects of the performance of shrimp aquaculture in Vietnam.